Latvia’s recipe - S. V. Zhdanov (Vestnik MGIMO-Universiteta, 2009)
This article contains the analysis of the results of socioeconomic development of the Republic of Latvia over the five-year period after joining the EU, distinct characteristics of economic policy of its Government during the current world crisis, as well as the evaluation of perspectives of Russian-Latvian interaction.